The Effect of Leadership, Work Culture and Competence on Service Performance with Motivation as an Intervening Variable on Health Workers at West Sumatra Pulmonary Hospital - Marwan Marwan; Elfiswandi Elfiswandi; Yulasmi Yulasmi (Sean Institute, 2026)
This study aims to examine the influence of leadership, work culture, and competence on service performance, with motivation as an intervening variable, among healthcare workers at the West Sumatra Lung Hospital. Data collection was conducted through a survey and questionnaire distribution, with a sample of 129 respondents. The analysis method used was structural equation modeling using SmartPLS. The results showed a significant influence of leadership on motivation. There was a significant influence of work culture on motivation. There was a significant influence of competence on motivation. There was a significant influence of leadership on service performance. There was an insignificant influence of work culture on service performance. There was an insignificant influence of competence on service performance. There was a significant influence of motivation on service performance. Motivation mediated the influence of leadership on service performance. Motivation mediated the influence of work culture on service performance. Motivation mediated the influence of competence on service performance.